The relationships of customer perceived value, customer satisfaction and customer loyalty: an emprical study - Sathana, V. (University of Colombo, 2011)
In today's world of intense competition, satisfying customers is only the base line, Management should focus on gaining customer loyalty with the customer satisfaction through increasing customer perceived value. This research intentionally focuses on the relationships among customer perceived value, customer satisfaction and customer loyalty, that is the proposed model indicates that delivering superior customer value can result in achieve high customer satisfaction, ultimately leading to consumer retention. Data were collected from 500 customers of retail-banking in Jaffna District by using structured questionnaires. Customer perceived value is analyzed through the benefits and cost of the service, then the benefits and cost were assessed by the product offering, customer services, relationship, image, buy price and other costs. Measures of customer loyalty were selected from length (retention) and depth (cross sell) of the bank-customer relationship. Length of relationship is reported by customer- reported relationship tenure. Relationship depth is measured by division cross-sell rates, as account cross sell or service cross sell. Simple correlation is used to examine the hypothesized relationships and also to increase the internal validity of the results; regression measures of customer perceived value, customer satisfaction and customer loyalty were examined. An important finding of this study that since customer satisfaction is related to customers' perceived value, banks should endeavor to satisfy every customer. Banks were wise to target and serve only those customers whose needs it met better than its competitors in a valuable manner. Customer satisfaction led to customer loyalty as the customers who were most likely to remain with that bank for long periods, who purchased multiple products and services, who recommended the bank to their friends and relations, but unsatisfied customer involved in customer complaints, when there was adequate level of responses to that complaints creates customer loyalty.
Keywords: Perceived Quality; Customer expectation; Customer Perceived Value; Customer Satisfaction; Customer loyalty